THE IMPACT OF LANOSA PRGORAM IMPLEMENTATION ON EMPLOYEE PERFORMANCE OF FRONTLINER EMPLOYEE IN PT. BANK NEGARA INDONESIA (PERSERO) TBK. KCU MANADO - Raturandang, Brenda (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Nowadays in globalization era, many foreign companies are willing to build their business in Indonesia. This is an opportunity for people in Indonesia to proof their performance to work. The main problem is about the Human Resource, because Human Resource Management is very important to control the company’s employee. The purpose of this study is to find out the impact of Lanosa (layanan nomor satu) program implementation on employee performance of frontliner employee in PT. Bank Negara Indonesia (Persero) Tbk. KCU Manado. 19 of the frontliner employee in PT. BNI (persero) Tbk. KCU Manado were surveyed as respondents. The result shows that skill has significant positive effect on employee performance, while attitude and appearance have positive influence but no significant effect on employee performance. The recommendation for this study are keep it up with their attitude , skill,  appearance on employee performance  and  give their extra skill performance  to customer to achieve the goals of Lanosa program. Keywords: attitude, skill, appearance and employee performance